Using multiple tuned mass dampers to control offshore wind turbine vibrations under multiple hazards. (15th June 2017) - Zuo, Haoran; Bi, Kaiming; Hao, Hong
Highlights: Propose using MTMDs for multi-hazard vibration control of offshore wind turbine. Detailed FE analyses are carried out to demonstrate the effectiveness of MTMDs. The robustness of the proposed method is demonstrated. Abstract: Offshore wind turbines can be built larger and lighter than they used to be due to the application of new materials. These large and flexible structures are vulnerable to external vibration sources such as wind, sea wave and earthquake excitations. It is necessary to mitigate the dynamic responses of offshore wind turbines to ensure the safety of these structures. Extensive research works have been carried out to mitigate the vibrations of the tower and/or blades of offshore wind turbines. Almost all the previous studies on the offshore wind turbine tower vibration control propose installing the control device at the top of the tower, i.e. in the nacelle. This method is effective to suppress the fundamental vibration mode of the tower, in which the maximum displacement occurs at the top of the tower. This practice is reasonable when wind and/or sea wave loadings are of interest since the energies of these vibration sources are concentrated in the low frequency range, and normally only the fundamental vibration mode of the tower is excited. On the other hand, offshore wind turbines may locate in the seismic prone areas, earthquake loading can be another vibration source during their lifetimes. When offshore wind turbines are subjected to earthquake excitation, higher vibration modes might be also excited. These higher vibration modes can further contribute to the structural responses and in certain circumstances they may even dominate the structural responses. In this case, installing the control device only in the nacelle will not be effective and more control devices should be installed at certain locations along the tower. In other words, one single control device will not be effective to control the tower vibrations if both the fundamental and higher vibration modes are of interest. This paper proposes using multiple tuned mass dampers (MTMDs) to control vibrations from the fundamental and higher modes of offshore wind turbine tower under multiple hazards, i.e. under the combined wind, sea wave and earthquake excitations. The effectiveness of the proposed method is numerically investigated. It should be noted that only the vibration of the tower is of interest in the present study. The vibration control of the blades is out of the scope of this paper, which will be further investigated.